Fucosterol, a Phytosterol of Marine Algae, Attenuates Immobilization-Induced Skeletal Muscle Atrophy in C57BL/6J Mice - Jieun Hwang; Mi-Bo Kim; Sanggil Lee; Jae-Kwan Hwang (Marine Drugs)
The objective of this study was to examine whether fucosterol, a phytosterol of marine algae, could ameliorate skeletal muscle atrophy in tumor necrosis factor-alpha (TNF-α)-treated C2C12 myotubes and in immobilization-induced C57BL/6J mice. Male C57BL6J mice were immobilized for 1 week to induce skeletal muscle atrophy. Following immobilization, the mice were administrated orally with saline or fucosterol (10 or 30 mg/kg/day) for 1 week. Fucosterol significantly attenuated immobilization-induced muscle atrophy by enhancing muscle strength, with a concomitant increase in muscle volume, mass, and myofiber cross-sectional area in the tibialis anterior (TA) muscle in mice. In both the TNF-α-treated C2C12 myotubes and the TA muscle of immobilized mice, fucosterol significantly prevented muscle protein degradation, which was attributed to a reduction in atrogin-1 and muscle ring finger 1 gene expression through an increase in forkhead box O3α (FoxO3α) phosphorylation. Continuously, fucosterol stimulated muscle protein synthesis by increasing the phosphorylation of the mammalian target of the rapamycin (mTOR), 70 kDa ribosomal protein S6 kinase, and 4E binding protein 1, which was mediated through the stimulation of the phosphatidylinositol 3-kinase (PI3K)/Akt signaling pathway. Thus, fucosterol alleviated skeletal muscle atrophy in TNF-α-treated C2C12 myotubes and immobilized C57BL/6J mice through the regulation of the Akt/mTOR/FoxO3α signaling pathway.